2021
DOI: 10.3390/microorganisms9081601
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with Altered Schaedler Flora Impacts Leukocyte Adhesion in Mesenteric Ischemia-Reperfusion Injury

Abstract: The microbiota impacts mesenteric ischemia-reperfusion injury, aggravating the interaction of leukocytes with endothelial cells in mesenteric venules. The role of defined gut microbiomes in this life-threatening pathology is unknown. To investigate how a defined model microbiome affects the adhesion of leukocytes in mesenteric ischemia-reperfusion, we took advantage of gnotobiotic isolator technology and transferred altered Schaedler flora (ASF) from C3H/HeNTac to germ-free C57BL/6J mice. We were able to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…FMT results indicated that the abundance of L. murinus in preoperative feces of patients is related to different sensitivities of mice to intestinal I/R injury. Altered Schaedler flora contains L.murinus-colonized mice reduced leukocyte deposition in mesenteric I/R injury as compared to conventionally raised specific pathogenfree controls mice [9]. More importantly, treatment with L. murinus significantly prevented intestinal I/R-induced intestinal injury and improved mouse survival, which may depend on macrophage involvement.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…FMT results indicated that the abundance of L. murinus in preoperative feces of patients is related to different sensitivities of mice to intestinal I/R injury. Altered Schaedler flora contains L.murinus-colonized mice reduced leukocyte deposition in mesenteric I/R injury as compared to conventionally raised specific pathogenfree controls mice [9]. More importantly, treatment with L. murinus significantly prevented intestinal I/R-induced intestinal injury and improved mouse survival, which may depend on macrophage involvement.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, L. murinus mediates anti-inflammatory effects in calorie-restricted mice [8]. Altered Schaedler flora contains L.murinus-colonized mice reduced leukocyte deposition in mesenteric I/R injury as compared to conventionally raised specific pathogen-free controls mice [9]. However, the role and mechanism of L. murinus in intestinal I/R injury remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative fasting by mimicking clinical requirements for patients was performed before the mouse model of intestinal I/R, and its alteration of flora metabolites was found beneficial for resisting intestinal I/R injury ( 84 ). Specific flora such as Bifidobacterium bifidum PRL2010 can attenuate intestinal I/R injury ( 85 ), and altered schaedler flora affected leukocyte adhesion in intestinal I/R injury ( 86 ). In terms of specific mechanisms, the flora metabolite pravastatin drives IL-13 release from type II innate lymphocytes via IL-33/ST2 signaling and attenuates intestinal I/R injury ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Altered Schaedler Flora (ASF) ( Bayer et al., 2021 ) can be considered to be a small model community allowing further investigations into multi-species metabolic cooperation. When simulated under contrasting dietary conditions, the emergent community behavior of ASF was seen to depend on the nature of the available nutrients (Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 99%